PEMANFAATAN HASIL FERMENTASI LIMBAH PUCUK TEH TEROKSIDASI SEBAGAI ALTERNATIF PUPUK ORGANIK UNTUK MENINGKATKAN KESEHATAN BIBIT TEH - Retno Muningsih; Andita Anggraini; Prana Hare Sri M (Universitas Teuku Umar, 2018)
Tea productivity influenced by technical culture, soil, climate conditions and planting material. Nursery is an initial stage of cultivation. The purpose of the nursery is to prepare quality planting material for rejuvenation and new plantings. To get quality seedling, needs good media and able to support early growth. Utilizing the waste from the tea processing plant in the form of tea leaves that are not eligible if to be fermented into organic fertilizer is then applied to the seedling tea. The results showed that seedling growth trend is increasing, the higher the plant the more the number of leaves that are formed and there is a positive linear relationship between plant height and number of leaves and leaf greenness. The results of the soil analysis showed that the availability of nutrients organic C, N, K and C/N ratio with moderate status, while the P content is very high.Keywords: organic matter, tea nursery, tea ocsidation